Statistical Machine Translation - Kumar, Mukesh; Vatsa, G.S.; Joshi, Nikita; Goswami, Sumit (DESIDOC Journal of Library & Information Technology, 2010)
Statistical Machine Translation (SMT) systems are based on bilingual sentence aligned data. The quality of translation depends on the data provided for translation learning. A huge parallel corpus is required for performing the statistical machine translation. The aim of this paper is to explore SMT using the Moses toolkit for creating a German-English translator. To perform the German to English translation, a parallel corpus of this language pair has been provided. Larger the size of the data provided for the training of the Moses decoder, more accurate is the translated output. DOI: 10.14429/djlit.30.457